Oblique Lateral Interbody Fusion vs. Minimally Invasive Transforaminal Lumbar Interbody Fusion for Lumbar Spinal Stenosis: A Retrospective Cohort Study - Gao, Quan-You; Wei, Fei-Long; Li, Tian; Zhu, Kai-Long; Du, Ming-Rui; Heng, Wei; Yang, Fan; Gao, Hao-Ran; Qian, Ji-Xian; Zhou, Cheng-Pei (Frontiers in Medicine, 2022)
Background: MIS-TLIF is an effective surgical option for LSS with spondylolisthesis. However, few studies have discussed OLIF. Objective: To evaluate postoperative improvements, complications, and reoperation rates between patients with lumbar spinal stenosis (LSS) undergoing oblique lateral interbody fusion (OLIF) or minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). Methods: We retrospectively studied 113 LLS patients who underwent OLIF or MIS-TLIF with percutaneous pedicle screw fixation between January 2016 and December 2018. We measured estimated blood loss, operative time, hospital stay, cost, reoperation, and complication incidence, visual analogue scale (VAS), Oswestry Disability Index (ODI), Japanese Orthopaedic Association (JOA), and Short Form-36 (SF-36) scores, discal and foraminal height and lumbar lordotic angle. Results: The mean age was 58.8±10.9 years. OLIF was costlier than TLIF (p=0.001); however, the TLIF group had increased operation time, blood loss, and hospital stays (p=0.007, 0.001, and 0.016, respectively). Postoperatively, VAS and ODI scores significantly decreased while JOA and SF-36 scores significantly increased. The postoperative differences in main outcomes between the groups were insignificant (all p>0.05). The OLIF group had the lowest rates of overall (9.8% OLIF vs. 12.9% MIS-TLIF), intraoperative (3.9% OLIF vs. 4.8% MIS-TLIF), and postoperative complications (5.9% OLIF vs. 8.1% MIS-TLIF), but the differences were insignificant (p=0.607, 0.813, and 0.653, respectively). The reoperation rate did not differ significantly (3.8% OLIF vs. 3.3% MIS-TLIF) (p=0.842). OLIF restored disc height (74.4% vs. 32.0%), foraminal height (27.4% vs. 18.2%), and lumbar lordotic angle (3.5% vs. 1.1%) with greater success than did MIS-TLIF. Conclusion Patients undergoing OLIF with LSS improved similarly to MIS-TLIF patients. OLIF restored disc height, foraminal height and lumbar lordotic angle more successfully than did MIS-TLIF. Keywords: Lumbar spinal stenosis; oblique lateral interbody fusion (OLIF); minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF); postoperative improvements